Levels of TAFI, TFPI and ADAMTS-13 in inflammatory bowel disease - Yüzbaşıoğlu, Bilgehan; Ustaoğlu, Müge; Yüzbaşıoğlu, Şule; Akbulut, Ulaş Emre; Özdil, Kamil (Turkish Journal of Gastroenterology, 2019)
Background/Aims: There is an increased tendency for thrombosis and thromboembolic complications in patients with inflammatory bowel disease (IBD). The aim of the present study was to determine the serum concentrations of thrombin-activatable fibrinolysis inhibitor (TAFI), tissue factor pathway inhibitor (TFPI) and a disintegrin and metalloproteinase with thrombospondin motif-13 (ADAMTS-13) in patients with IBD and to assess their possible role in the etiopathogenesis of the disease.Materials and Methods: Thirty-four patients with IBD (23 ulcerative colitis and 11 Crohn’s disease) and 20 healthy controls were included in the present study. TAFI, TFPI, and ADAMTS-13 concentrations were determined by enzyme-linked immunosorbent assay.Results: Mean TAFI, TFPI, and ADAMTS-13 concentrations in the patient group were 17.75 ng/ml, 72.10 ng/ml, and 14.90 U/l, respectively. In the control group, these values were 117.10 ng/ml, 300 ng/ml, and 191.55 U/l, respectively. TAFI, TFPI, and ADAMTS-13 values were significantly lower in the patient group than in the control group (all p<0.01).Conclusion: TAFI, TFPI, and ADAMTS-13 levels were significantly lower in the patient group. These findings indicate the presence of a clear, multifactorial imbalance in the coagulation–fibrinolytic system in the patient group. It is also possible that this imbalance in the coagulation and fibrinolytic system may play a role in the still unclear etiopathogenesis of the disease.